HUBUNGAN STATUS GIZI DENGAN PROSES PENYEMBUHAN LUKA DI RSUD H. ANDI SULTHAN DAENG RADJA KABUPATEN BULUKUMBA - Fitriani; Tenriwati (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2017)
At present, the incidence of injuries in Indonesia is quite high, as seen from data on traffic accidents in the general public. There are several factors that affect wound healing, one of which is nutritional status. Based on the preliminary data retrieval conducted by researchers in the seruni surgery room in the last 1 month namely in March, it was found that the number of wounded patients was 109 patients, where the number of men was 78 (71.56%) while the number of women was 31 ( 28.44%) The purpose of this study was to determine the relationship between nutritional status and the wound healing process in RSUD. H. Andi. Sulthan Daeng Radja Kab. Bulukumba. This research uses the type of design of this research is quantitative research. This type of research uses analytic observational research with cross sectional approach. The sample of this study were 41 respondents taken by purposive sampling method. Data analysis in this study used the chi-square test (chi square test). The results of the analysis used the chi-square statistical test with a confidence level (α = 0.05). Based on the results of this test, the p value is 0.001, thus p <α (0.001 <0.05), then Ho is rejected and Ha is accepted. The conclusion of this study is that there is a relationship between nutritional status and the process of wound healing in RSUD. H. Andi. Sulthan Daeng Radja Kab. Bulukumba. Researchers suggest that this study be used as a material consideration in the fulfillment of nutrition in wound care patients in RSUD.H.A. Sulthan Daeng Radja Kab. Bulukumba and this research can be continued by conducting research related to the wound healing process and linking it with other variables.